Transplanted human cord blood-derived unrestricted somatic stem cells preserve high-energy reserves at the site of acute myocardial infarction - Ghodsizad, Ali; Ungerer, Matthias; Bordel, Viktor; Kallenbach, Klaus; Kögler, Gesine; Bruckner, Brain; Niehaus, Michael; Gregoric, Igor; Karck, Matthias; Ruhparwar, Arjang (Cytotherapy, 2011)
Background aims - It has been demonstrated that transplantation of human cord blood-derived unrestricted somatic stem cells (USSC) in a porcine model of acute myocardial infarction (MI) significantly improved left ventricular (LV) function and prevented scar formation as well as LV dilation. Differentiation, apoptosis and macrophage mobilization at the infarct site could be excluded as the underlying mechanisms. The paracrine effect of the cells is most likely to be observed as the cause for the USSC treatment. The aim of our study was to examine the cardiomyocyte metabolism and the role of high-energy phosphates at the marginal infarct. - Methods - USSC were transplanted into the myocardium of the LV, which was supplied by a ligated circumflex artery. Forty-eight hours later, the hearts were harvested and biopsies were performed from the marginal infarct zone surrounding the site of the cell injection. The concentrations of creatinine phosphate (CP), adenosine monophosphate (AMP), adenosine diphosphate (ADP) and adenosine triphosphate (ATP) were determined by chromatography. - Results - The concentration of ADP, ATP and CP in the marginal zone of the infarction was significantly higher in the USSC group. The mean global left ventricular ejection fraction (LVEF) (SD) was 64% (8%) before MI; post-MI, LVEF decreased to 35% (9%). - Conclusions - Preservation of high-energy phosphates in the marginal infarct zone suggests that the preservation of energy reserves of surviving cardiomyocytes is a possible mechanism of action of transplanted stem cells in acutely ischemic myocardium.